SEJARAH PERKEMBANGAN TAFSIR AL-QUR'AN - Hamdan Hidayat (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2020)
Interpretation of the Qur'an has occurred at the time of the Prophet Muhammad was still alive. When the Prophet Muhammad received revelations from God then delivered to the sahabat, it was the same when the Prophet Muhammad delivered the interpretation of a particular verse to the sahabat and those who asked the purpose of a particular verse, then the Prophet Muhammad answered it. After the Prophet Muhammad died, the development of interpretation then continued at the time of the Companions, Tabi'in and so on, by the method of the Qur'an, Hadith and Companions of Companions, because the main source was gone. Interpretation during this time of sahabat began to experience significant development, because the sahabat began to look for explanations of the Koran based on the explanation of the Prophet Muhammad, whether it came from the Koran or from the hadiths, if no interpretation is found, then Companions commit ijtihad. The development of further interpretations in the time of tabi'în, tabi'i al-tabi'în, 'long-time salaf al-shali'in, and' long-time khalifa (contemporary) with various methods, patterns and characteristics of its own.